Acetylene Radical-Cations in Carbon-Carbon Bond Forming Reactions - V. Vasilyev, Aleksander (Mini-Reviews in Organic Chemistry, 2017)
This review surveys carbon-carbon bond forming reactions of acetylene radical-cations, generated under the one-electron oxidation of alkynes in the systems lead dioxide (PbO2) – strong acid (CF3CO2H, FSO3H, HF). The oxidative dimerization proceeds very regioselectively at acetylene carbons. This approach is a powerful synthetic tool, leading to complex and polyfunctional organic molecules, such as, dicarbonyl- and tetracarbonyl-substituted ethylenes, 1,4-difluoro- and 1,4- dichlorobutadienes, etc. Reaction mechanisms of acetylene radical-cations are considered. The reactivity of acetylene radical-cations may be explained by their electronic structure, determined by means of electron spin resonance spectroscopy and cyclic voltammetry.
Keywords: carbon-carbon bond forming reactions